Material Stone : Constructions and Technologies for Contemporary Architecture - Mackler, Christoph (ed.) (Birkhauser, 2004)
The Work of Material Stuffs, Regarded "Superficially"; Technology, Industrialisation, Materiality, Simplicity; Stone and Semplance; Extraction and Working of Natural Stone Products; Building with Stone; Questions of Artistic Tact; Restoration and Maintenance; Cast Reconstructed Stone; Brick and Clinker; and Illustrations of Selected Varieties of Natural Stone.